PENGARUH PEMBERIAN BIOCHAR TERHADAP BEBERAPA SIFAT BIOKIMIA TANAH DAN PERTUMBUHAN TANAMAN BAWANG MERAH PADA LAHAN TERCEMAR RESIDU PESTISIDA - Sonni Senna Dimas Airlangga; Mochammad Munir; P Poniman (Jurnal Tanah dan Sumberdaya Lahan, 2021)
The production of shallots in Brebes has not been significantly free from the use of chemical pesticides. Preventive land contaminated with pesticides needs to be done, one of which is through the improvement of polluted land using biochar. The study was aimed to determine the effectiveness of the effect of urea plus nano biochar and urea plus biochar enriched by microbial consortia on the status of C-organic, pH, and soil microbial populations and their effects on profenofos residues. The experiment was designed with a Randomized Block Design with 5 treatments including: P (without biochar and microbes), B (Urea plus biochar), BM (Urea plus biochar and microbial), NB (Urea plus nano biochar), NBM (Non-biochar and microbial) Urea added with nano biochar and microbes), and repeated 4 times, so that the number of research units was 20 units. The microbes used in enriching urea plus biochar are microbial consortia, Stenotrophomonas maltophilla, Achromobacter denitrificans, Bacillus cereus, Bacillus subtilis, Bacillus thuringiengsis and Bacillus aryabathai. The results of the study include, the administration of urea plus biochar and nano biochar with microbial consortia did not have a significant effect on pH, C-organics, soil microbial populations and profenofos residues. At 35 and 63 DAP the highest pH of treatment B was 5.84, and 6.53. Organic C-35 and 63 DAP at low criteria are 1.12 - 1.30%. The highest microbial population of 35 and 63 DAP in treatment B was 485 x 106. The highest growth rate of plant length in the BM treatment with a value of 6.06 cm week-1, while the growth rate of the number of leaves in the BM treatment had a higher yield compared to other treatments , with a value of 2.88 strands week-1.